2008
DOI: 10.1007/s00167-008-0678-8
|View full text |Cite
|
Sign up to set email alerts
|

Is there significant variation in the material properties of four different allografts implanted for ACL reconstruction

Abstract: The aims of our study were to: (1) determine if there are differences in the material properties of tendon obtained from implanted tibialis anterior, achilles, bone-patella- bone and tibialis posterior allografts; (2) determine the variability in material properties between the implanted specimens. A total of 60 specimens were collected from fresh frozen allografts implanted at ACL reconstruction. Specimens collected included 15 tibialis anterior, 15 tibialis posterior, 15 achilles and 15 bone-patella-bone ten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
2
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 37 publications
0
16
2
1
Order By: Relevance
“…To consider the cross-sectional areas as rectangular may compromise the measurements [1,24]. Our setup with digital scan resulted in a low standard deviation, as compared to similar tests of Shim et al [37] or Penn et al [35] ( Table 2). The low standard deviation may be interpreted as another result of minimizing material slippage at the specimen-clamp interface.…”
Section: Application Of Partial Plastination: Young's Modulus Of the mentioning
confidence: 85%
See 2 more Smart Citations
“…To consider the cross-sectional areas as rectangular may compromise the measurements [1,24]. Our setup with digital scan resulted in a low standard deviation, as compared to similar tests of Shim et al [37] or Penn et al [35] ( Table 2). The low standard deviation may be interpreted as another result of minimizing material slippage at the specimen-clamp interface.…”
Section: Application Of Partial Plastination: Young's Modulus Of the mentioning
confidence: 85%
“…However, freezing the specimens for storage does not alter the YM in the defrosted state [36]. Another approach is to investigate bone-specimen-bone allografts [17,35,37,38]: Bone-specimen-bone allografts do not reflect the YM of the specimen solely, because specimens such as the tract insert to the bone via fiber cartilage [14,39]. Shim et al obtained YM values of allografts with a low standard deviation for the transverse ligament of the atlas (294.24 ± 13.97 N/mm 2 [37]).…”
Section: Avoiding Materials Slippage By Partial Plastinationmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the anatomy and lamellar architecture of AF, it is difficult to examine variation in mechanical properties by tensile testing as it can be undertaken like a tendon. We thus designed a bone-AF-bone specimen, to examine the differences in the mechanical properties before and after decellularization by tensile testing, using a testing protocol based on work by Woo et al and Penn et al [ 19 , 20 ]. Two parallel bone-AF-bone specimens were obtained from the same level disc and adjacent vertebrae with a width of 5 mm, depth of 8 mm, and bone stump length of approximately 15 mm (Figure 1 A).…”
Section: Methodsmentioning
confidence: 99%
“…48 Despite the popular use of allografts, there is a paucity of data regarding variability in biomechanical properties of processed allografts that are used intraoperatively. 34,52 A study of Achilles allografts by Penn and colleagues 34 showed significant variability in material properties in nonirradiated Achilles allograft. However, to the best of our knowledge, no prior studies have examined the variation in the material properties of low-dose irradiated Achilles allograft used in the operating room for ACLR.…”
mentioning
confidence: 99%